IMPLEMENTATION OF GOVERNANCE IN VILLAGE FUND MANAGEMENT IN ILOMATA VILLAGE, BULANGO ULU DISTRICT, BONE BOLANGO REGENCY - Danial Yunus; William Indra S. Mooduto; Sitti Husna Djou (Jurnal Ilmu Manajemen dan Bisnis, 2021)
This study aims to find out a descriptive description of the implementation ofgovernance in the management of village funds which will ultimately affect theimplementation of village governance.This research is a qualitative research with primary data and secondary data.Primary data obtained through observation, interviews and documentation.Secondary data using literature study.As for the results of the research conducted, it shows that the management ofvillage fund budgets must be based on the principles of Good Governance in thevillage whose management is a whole activity covering the stages and processesthat have been regulated, namely the initial activity is the participatory planningstage, the implementation that meets transparency, and accountability processesfor village fund budgets (ADD)